THE IMPLEMENTATION EFFECT OF PEER TEACHING FLIPPED CLASSROOM ON STUDENT'S UNDERSTANDING OF MATHEMATICAL CONCEPTS IN LEARNING MATHEMATICS - Lydia Hendayani Sukma; Ramadoni Ramadoni; Mulia Suryani (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This research is motivated by the low understanding of students' mathematical concepts in the mathematics learning process. The purpose of this study was to find out how the influence of the Peer Teaching Flipped Classroom learning model on mathematical concept understanding, and the influence of Peer Teaching Flipped Classroom in terms of academic ability level on the student’s mathematical concept understanding ability in class XII IPA3 SMAN 1 X Koto Tanah Datar Regency. This type of research is a quantitative nonequivalent pretest-posttest experiment. Where the research subjects were students of class XII IPA SMAN 1 X Koto Kab. Tanah Datar for the 2022/2023 academic year, totaling 44 students. The instrument used to collect data is in the form of test questions. The results of this study indicate that students have an increase in answering questions. Based on data analysis obtained F(1.42) and p=0.001 <0.05 then H0 is rejected, which means that there is an influence of Peer Teaching Flipped Classroom on understanding mathematical concepts of class XII IPA3 students of SMAN 1 X Koto Kab. Tanah Datar. However, the level of students' academic ability did not have a significant effect on understanding mathematical concepts with the application of Peer Teaching Flipped Classroom. It is seen from the analysis of the data obtained p = 0.051> 0.05, then H0 is accepted.